1996
DOI: 10.1016/s0925-4439(96)00056-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tumor necrosis factor-a (TNF-a) levels in Gaucher disease

Abstract: Tumor necrosis factor-a (TNF-a) levels were measured in the plasma of patients with different types of Gaucher disease (GD) and patients with other lysosomal storage diseases. The highest TNF-a levels were observed in the most severe neuronopathic type of GD, exceeding those found in healthy individuals as well as patients with other lysosomal disorders. Type I GD cases showed a wide range of TNF-a levels ranging from normal to 2.5 x the highest control value. TNF-a is a pleiotropic cytokine produced mainly by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 17 publications
3
46
0
2
Order By: Relevance
“…The fact that the plasma levels of IL6 and TNFa are normal does not exclude the possibility that concentrations of these cytokines in the vicinity of the Gaucher macrophages are abnormally high. In this respect, it is of interest to mention that elevated plasma levels of TNFa have been found in the more severe type 2 and 3 forms of Gaucher disease and to a lesser extent in some type 1 Gaucher disease patients (9). In another recent study no elevations in TNFa concentrations in type 1 disease could be established (10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that the plasma levels of IL6 and TNFa are normal does not exclude the possibility that concentrations of these cytokines in the vicinity of the Gaucher macrophages are abnormally high. In this respect, it is of interest to mention that elevated plasma levels of TNFa have been found in the more severe type 2 and 3 forms of Gaucher disease and to a lesser extent in some type 1 Gaucher disease patients (9). In another recent study no elevations in TNFa concentrations in type 1 disease could be established (10).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, in vitro stimulation of murine macrophages with glucosylceramide has revealed enhanced production of IL1 (8). Recently, elevated plasma levels of TNFa were reported in some patients with Gaucher disease (9). In another study, increased levels of IL6 and IL10, but not of TNFa and IL1, were established (10).…”
Section: Introductionmentioning
confidence: 99%
“…This lysosomal storage leads to the characteristic engorged macrophages, known as Gaucher macrophages (GMs) or ‘Gaucher cells’ (Machaczka et al ., 2011), and contributes to the organomegaly, bone disease and cytopenia typically encountered in patients with GD. Furthermore, glycolipid accumulation and lysosomal dysfunction in GD serve to prime macrophages to release pro‐inflammatory cytokines in response to stimuli (Michelakakis et al ., 1996; Allen et al ., 1997; Barak et al ., 1999). Thus, GMs provide a unique model to explore the mechanisms underlying defective erythrophagocytosis and its relationship to inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that Gaucher disease (GD) might be accompanied by low-grade, subclinical, and smoldering internal inflammation [1][2][3][4][5]. This low-grade inflammation might be accompanied by the appearance of enhanced concentrations of adhesive macromolecules in the peripheral blood [6].…”
Section: Introductionmentioning
confidence: 99%